Lower Education and Household Income Contribute to Advanced Disease, Less Treatment Received and Poorer Prognosis in Patients with Hepatocellular Carcinoma - Shen, Yuan (J Cancer, 2017)
Understanding the ways in which socioeconomic status affects prognosis of hepatocellular carcinoma (HCC) is important for building up strategies eliminating the inequalities in cancer diagnosis and treatments among different groups, which, remains undetermined. In the present study, 1485 newly diagnosed HCC patients with complete demographic and clinical data were included. Socioeconomic data, including education, annual household income and residency was also reported by patients or families. In the present study, less educated patients were older, more female involved, poorly paid, more living in rural places, had more advanced tumor burden, received less curative and loco-regional therapies, and thus showed poorer short-term and long-term outcomes (in total or after surgical resection) than the highly educated. Patients with lower income were less educated, less treated, and more likely to live in rural places, had more advanced stages of HCC and thus poorer long-term survival (in total or after surgical resection) than higher income groups. In Cox regression analysis, lower household income was independently associated with poorer outcome (HR=1.2, 95% CI: 1.0-1.4, p=0.036). These results indicate that education and income are critically associated with early diagnosis, treatments and prognosis of HCC. Much more efforts should be taken to support the patients with less education and lower income to improve the outcomes of HCC.